Islam's encounter with English and Ismail al-Faruqi's concept of Islamic English: A postcolonial reading - Hasan, Md. Mahmudul (The International Institute of Islamic Thought, 2014)
In the past, many Muslims maintained strong reservations about using English as a means of communication, interaction, and intellectual practices mainly due to its association with British colonialism. In the postcolonial world Muslims and other religious communities, as well as various ethnic and indigenous groups, have moved away from the ideological and political assumptions of a binary relationship between English and their cultural and religious identities. As a result, several hundred million Muslims now use English as their first or second language, and more books on Islam are published in it than in any other language. However, Ismail al-Faruqi (1921-86) sees a serious anomaly in how Muslim names and Islamic theological terms are transliterated and translated, as the dominant practice shows not a loyalty to meaning, but to the norms of the target language. Such an approach causes these names and terms to lose semantic associations and religious connotations. To rectify this, al-Faruqi proposes the introduction of “Islamic English.” Based on his linguistic diagnosis and remedy, I will discuss this approach from a postcolonial perspective.